If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5d + -1c = 12 Reorder the terms: -1c + 5d = 12 Solving -1c + 5d = 12 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5d' to each side of the equation. -1c + 5d + -5d = 12 + -5d Combine like terms: 5d + -5d = 0 -1c + 0 = 12 + -5d -1c = 12 + -5d Divide each side by '-1'. c = -12 + 5d Simplifying c = -12 + 5d
| 8(9x+9)+9(11-x)= | | (4x+1)+(11-4x)= | | 35+50x= | | (4x+13)+(8x-5)= | | 7(8x+5)= | | 3x-5x=-9+x | | 2x^4+7=47 | | 2a+7b-3b+a= | | m+50x=35 | | f(x)=-16x+160x | | 6x+x-8=6x+5 | | 3.2=125x | | 8m-2m=72 | | 5g-5=7 | | -5=-19-n/7 | | 13x-60=83 | | x^6+7x^5+2x^4+9x^3+10x^2-12x-15=0 | | 2/5(x-15)=500 | | c/7+5=-6 | | 24k^2=-24k | | 3x-4x+x-6+2x= | | 8x^2+72a-81=0 | | v/4-9=-3 | | 44-17x=15.60 | | (x+21)+2x=136 | | 2x^2-2x=3x^2-9x | | 180=a+2a+15+a-35 | | (x+21)-2x=136 | | -2=(-2x-8) | | 3/4(8b-4)=-2 | | 2y^2-8y+9-12y^2-8y+3= | | 4(-a+4)=12 |